Catalytic Cracking of Methyl Ester from Used-Cooking Oil Using Ni-Impregnated Active Charcoal Catalyst - Nazarudin Nazarudin; Ulyarti Ulyarti; Oki Alfernando; Yogie Yogendra Hans (Dept. of Chemical Engineering, Diponegoro University, 2022)
Current petroleum energy sources have been starting to diminish along with the increasing a demand in industries and transportations. In the next few years Indonesia is predicted to experience a fuel crisis. One way to solve this problem is to find the alternative energy sources from renewable raw materials. This study was conducted to obtain alternative renewable energy sources through catalytic cracking of used cooking oil-derived methyl ester into biofuel using active charcoal catalyst. The active charcoal was made out of solid waste (shells) of the oil palm industry. Nickel solutions of varying concentrations (1%, 2%, 3%) ware impregnated into active charcoal to produce the Ni- charcoal catalyst. This catalyst was then used for catalytic cracking of methyl esters with variations in the reaction temperature of 400oC, 450oC and 500oC. The Methyl ester was produced from filtered used-cooking oil by transesterification method. SEM-EDX analysis showed that Nickel metal was successfully embedded into active charcoal where the highest concentration of Nickel (18.4%) was found at a impregnation treatment using 2% of Nickel solution. From the SEM image, it can also be seen that the catalyst produced unique pores. The gravimetric analysis of the catalytic cracking product showed that the highest fraction of oil liquid resulting from catalytic cracking at 400oC using Ni-charcoal catalyst impregnated with 3% Nickel solution.